PERSISTENCY ANALYSIS OF CYCLONE HISTORY IN ARABIAN SEA - Hussain, M. A.; Abbas, S.; K. Ansari, M. R. (The Nucleus, 2011)
As we know that tropical cyclones (or hurricanes) act as giant heat engines, so it is logical to assume that an increase in sea surface temperatures (SSTs) will create more intense hurricanes. Indeed, there is a general consensus among hurricane scientists that an increase in SSTs due to global warming, should, in theory, lead to more intense hurricanes. This paper discusses the tropical cyclones history in Arabian Sea with respect to trend, underlying distribution of occurrence of tropical cyclones in 120 years (1891-2010), and its persistency / antiâˆ’persistency with the help of Hurst exponent calculations. We test for presence of any positive trend in cyclones frequency in the Arabian Sea by analyzing the cyclone data of 120 years. It has been shown that there exists a statistically significant positive trend in Arabian Sea cyclone frequency data. The underlying distribution of occurrence of tropical cyclones history came out to be lognormal, suggesting an increasing multiplicative complex physical process, which strengthens the finding of positive trend in cyclone frequency data. Hurst exponent of Arabian Sea annual cyclone frequency for 120 years came out to be 0.98, which shows a persistency in future cyclone frequency and bolsters the results of trend and distribution function of cyclone frequency history. Moreover, cyclone trend values of 120 years data for the months of May, June, October, and November are also significant. Finally, sea surface temperatures for these months also reveal persistency as the values of Hurst exponent are greater than 0.5 and seems to be proportional to the cyclone frequency slope (of fitted trends) values for the same months.